Twelve tips for interfacing with the new generation of medical students: iGen. (2nd November 2021) - Lerchenfeldt, Sarah; Attardi, Stefanie M.; Pratt, Rebecca L.; Sawarynski, Kara E.; Taylor, Tracey A. H.
Abstract: iGen, or Generation Z, is the newest generation of health professions students to enter the classroom. This generation represents the first cohort of students in which technology has been present in all aspects of their lives. Since birth, they have been influenced by the boom of social media and wide-spread internet availability, leading to decreased face-to-face interactions and a desire for immediate access to information. Health professions educators should recognize the unique attributes of iGen students in order to foster student success and create a more positive learning environment. The following twelve tips examine the research-based distinctive characteristics of iGen students and highlight important concepts to consider when modifying current pedagogy to better support their needs. Incorporating these tips as an educator can promote lifelong learning and skill development for iGen students and empower this generation to thrive.